Recovery of insular seabird populations years after rodent eradication - Martin Philippe‐Lesaffre; Martin Thibault; Stephane Caut; Karen Bourgeois; Tristan Berr; Andreas Ravache; Eric Vidal; Franck Courchamp; Elsa Bonnaud (Conservation Biology, 2023)
Seabirds have been particularly affected by invasive non‐native species, which has led to the implementation of numerous eradication campaigns for the conservation of these keystone and highly vulnerable species. Although the benefits of eradication of invasive non‐native species for seabird conservation have been demonstrated, the recovery kinetics of different seabird populations on islands after eradication remains poorly evaluated. We conducted long‐term monitoring of the number of breeding pairs of seven seabird species on a small atoll, Surprise Island, New Caledonia (southwestern tropical Pacific). Marine avifauna of the island were surveyed yearly 4 years before to 4 years after rodent eradication (conducted in 2005), and we conducted multiple one‐time surveys from ∼10 years before and ∼15 years after eradication. We sought to determine how different seabird species responded to the eradication of invasive rodents in an insular environment. Three species responded positively (two‐ to 10‐fold increase in population size) to eradication with differences in lag time and sensitivity. The number of breeding pairs increased (effect sizes = 0.49–0.95 and 0.35–0.52) for two species over 4 years post‐eradication due to immigration. One species had a longer (at least 5 years) response time than all others; breeding pairs increased for over 10 years after eradication. Long‐term sampling was necessary to observe the responses of the seabird populations on the island because of the delayed response of a species to eradication not visible in the first years after eradication. Our results confirmed the positive effects of eradication of invasive non‐native species on seabirds and emphasize the importance of mid‐ and long‐term pre‐ and posteradication surveys to decipher the mechanisms of seabird recovery and confirm the benefits of eradication for conservation purposes.

Native predators living in invaded areas: responses of terrestrial amphibian species to an Argentine ant invasion - Paloma Alvarez-Blanco; Stephane Caut; Xim Cerdá; Elena Angulo (Oecologia, 2017)